Brain organoids: Establishment and application - Chen, Hao; Jin, Xin; Li, Tie; Ye, Zhuang (Frontiers in Cell and Developmental Biology, 2022)
Organoids cultured in vitro are mainly differentiated from adult stem cells and pluripotent stem cells. Various types of organoids such as gut, brain, and liver have been successfully cultured. As an emerging research model that simulates the development of human organs and the occurrence and development of diseases, it has been widely applied in disease modeling, screening of anticancer drugs, and gene therapy. Here, we mainly focus on the brain organoids and review the development of brain organoids and their progress in exploring brain development, disease modeling, and drug screening.